Accuracy of the Eosinophilic Esophagitis Endoscopic Reference Score in Diagnosis and Determining Response to Treatment - Dellon, Evan S; Cotton, Cary C; Gebhart, Jessica H; Higgins, Leana L; Beitia, RoseMary; Woosley, John T; Shaheen, Nicholas J (Clinical gastroenterology and hepatology, 2016)
Little is known about the diagnostic utility of the Eosinophilic Esophagitis (EoE) Endoscopic Reference Score (EREFS), and how scores change in response to treatment. We investigated the operating characteristics of the EREFS in diagnosis of EoE, how the score changes with treatment, and ways to optimize scoring system. We performed a prospective study of adults undergoing outpatient upper endoscopy from August 2011 through December 2013 at the North Carolina School of Medicine. Incident cases of EoE were diagnosed per consensus guidelines and were treated with topical steroids or dietary elimination (n = 67); 144 subjects without EoE were included as control subjects. EREFS scores were compared between cases and control subjects. For EoE cases, scores were compared before and after treatment. Area under the receiver operator characteristic curve analysis was used to determine diagnostic utility of the EREFS system. An iterative analysis was performed to determine optimal EREFS scoring weights. The mean total EREFS score was 3.88 for EoE cases and 0.42 for control subjects (P > .001); the score identified subjects with EoE with an area under the receiver operator characteristic curve of 0.934. After treatment of EoE cases, the mean score decreased from 3.88 to 2.01 (P > .001). This change was more prominent for patients with a histologic response (reduction to <15 eosinophils per high-power field) compared with nonresponders; posttreatment scores were 0.45 for responders versus 3.24 for nonresponders (P < .001). A weighted scoring system that doubled exudates, rings, and edema scores maximized the responsiveness of the total EREFS score. The EREFS classification system identifies patients with EoE an area under the receiver operator characteristic curve of 0.934; the score decreases with treatment, and histologic responders have significantly lower scores than nonresponders. This system can therefore be used to identify individuals with EoE and used as an endoscopic outcome measure to follow their response to treatment.